(untitled) (Journal Intellectual Sufism Research (JISR), 2024)
Abstract. The history of Islamic enducation began when the Prophet Muhammad SAW was appointed as an Apostle, then continued with Khulafaur Rasyidin. These leaders really understand that education is the main key to building a strong, civilized and advanced society. During the time of Khulafaur Rosyidin there were developments in Islamic education, especially during the time of Ustman bin Affan. The purpose of writing this article is to find out the implications in managing Islamic education during the time of Ustman bin Affan in the modern world. The method used in writing this article is the review papers method. During his leadership, Ustman bin Affan implemented a popular and simple model of Islamic education. Form groups of students As an educational object, various methods are adapted to each group. Ustman bin Affan’s famous work is the Book of the Koran which is usually called the Ottoman Mushaf. During that time he played an important role in creating the educational curriculum. For these implications, he is still relevant in the thoughts and policies applied to Islamic education and this can be used as a reference for the development of the Islamic education system in the modern era.